2017
DOI: 10.1080/16070658.2017.1267380
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between obesity, leptin, adiponectin and the components of metabolic syndrome in urban African women, Free State, South Africa

Abstract: Objectives: Obesity prevalence is increasing worldwide. In South Africa, older and urbanised African women have significantly higher rates of obesity. Limited information is available on the relationship between anthropometric parameters, adipokines and metabolic health status of African women. This study investigated the relationship between obesity, adipokines and the components of metabolic syndrome in urban African women. Methods: This study included 135 urban African women that were 26-63 years of age, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
3
8
1
1
Order By: Relevance
“…Nevertheless, contrary to them, no significant correlation was found between glucose levels and LAR. Zyl et al [ 29 ] found similar results in their study on South African urban women, although LAR was significantly higher in women with elevated blood glucose. This finding seems to be specific to Africans.…”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, contrary to them, no significant correlation was found between glucose levels and LAR. Zyl et al [ 29 ] found similar results in their study on South African urban women, although LAR was significantly higher in women with elevated blood glucose. This finding seems to be specific to Africans.…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that decreased circulatory levels of adiponectin in obesity (despite being produced in adipose tissue) are inversely correlated with body fat percentage in adults 17 . Our study was in agreement with the results of Van Zyl et al, (2017) 18 and Fruhbeck et al, (2018) 19 whom found that the serum level of Adiponectin was significantly lower in obese patients.…”
Section: Discussionsupporting
confidence: 94%
“…From the literature, it is already known that the ratio between leptin and adiponectin is an important parameter that can be used to indicate the risk of developing obesity and even metabolic syndrome [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin and leptin are mainly secreted by the adipose tissue and inhibit feeding by different mechanisms, acting on their respective receptors (AdipoRs and LepRs) located in neurons in the hypothalamus [18]. These adipokines levels are important indicators for the development of obesity and metabolic syndrome, since there is a reduction in the endogenous concentrations of adiponectin and an increase in leptin levels in overweight and obese individuals [19,20].…”
Section: Introductionmentioning
confidence: 99%